The application of laboratory-based analytical tools and techniques for the quality assessment and improvement of commercial antivenoms used in the treatment of snakebite envenomation - Patra, Aparup (2021)
Snakebite envenomation is a public health problem of high impact, particularly for the developing world. Antivenom, which contains whole or protease-digested immunoglobulin G, purified from the plasma of hyper-immunized animals (mainly horses), is the mainstay for the treatment of snakebite envenomation. The success of antivenom therapy depends upon its ability to abrogate or reduce the local and systemic toxicity of envenomation. In addition, antivenom administration must be safe for the patients. Therefore, antivenom manufacturers must ensure that these products are effective and safe in the treatment of envenomations. Antivenom efficacy and safety are determined by the physicochemical characteristics of formulations, purity of the immunoglobulin fragments and antibodies, presence of protein aggregates, endotoxin burden, preservative load, and batch to batch variation, as well as on the ability to neutralize the most important toxins of the venoms against which the antivenom is designed. In this context, recent studies have shown that laboratory-based simple analytical techniques, for example, size exclusion chromatography, sodium dodecyl sulphate polyacrylamide gel electrophoresis, mass spectrometry, immunological profiling including immuno-turbidimetry and enzyme-linked immunosorbent assays, Western blotting, immune-chromatographic technique coupled to mass spectrometry analysis, reverse-phase high performance liquid chromatography, spectrofluorometric analysis, in vitro neutralization of venom enzymatic activities, and other methodologies, can be applied for the assessment of antivenom quality, safety, stability, and efficacy. This article reviews the usefulness of different analytical techniques for the quality assessment of commercial antivenoms. It is suggested that these tests should be applied for screening the quality of commercial antivenoms before their preclinical and clinical assessment.